Fundamentação da decisão judicial: a aplicabilidade do art. 489, §1º e §2º do Código de Processo Civil à luz da teoria analítica do direito de Robert Alexy - Barboza, Laís Ramos (2018)
The present study has as object of study the duty to justify the judicial decisions established in art. 489 of the Brazilian Code of Civil Procedure, which, in accordance with the Federal Constitution, established the grounds as an essential element of the judicial pronouncement, but innovated in the conception of §1º which deals with the inherent contours of the obligation to state reasons, and §2º which provides for the justification of a consolidated judicial decision in the weighting of legal rules. Seen in this way is that once consolidated in the judicial decision the preponderance of the implementation of legal norms, the legitimation of the exercise of the judicial activity and thus the guarantee of correction of the legal discourse by means of its consistency is in the duty of justification of the judicial decision an important tool to control the interpretation and application of legal norms. Thus, in view of the dimension of the thematic, several theories were developed in order to better clarify the phenomenon described and with that to trace parameters of its verification, among these the present work took as object of investigation the doctrine undertaken by the German Robert Alexy, which widely received in Brazil has as theoretical framework the development of an argumentative legal theory, besides being responsible for the introduction of the weighting technique as a form of resolution of the normative conflict between principles. For this reason, the purpose of this study is to analyze the duty to state reasons for the judicial decision, set forth in art. 489, §1º and §2º in the light of the discursive theory developed by Alexy, in order to draw the parallel between the theoretical framework chosen and the regulation of the thematic. Such an approach presupposes the necessary verification of the compatibility of that with the current procedural system, so that its scope and limitations are established.